(untitled) (World Bulletin of Public Health, 2024)
Non-developing pregnancy is a special form of pregnancy failure in which the embryo (foetus) dies in the early stages of gestation. The most common causes of undeveloped pregnancy are chromosomal abnormalities, poor lifestyle, infectious factors, including sexually transmitted infections, genetic mutations and uterine abnormalities, maternal endocrine and immunological disorders and chronic endometritis. Ignoring or insufficiently considering possible aetiological factors and conditions contributing to miscarriage increases the risk of recurrent reproductive losses.